Performance analysis of lead-free CsBi3I10-based perovskite solar cell through the numerical calculation - Ahmmed, Shamim; Karim, Md. Abdul; Rahman, Md. Hafijur; Aktar, Asma; Islam, Md. Rasidul; Islam, Ashraful; Bakar Md. Ismail, Abu (Solar energy, 2021)
[Display omitted] •The performance of eco-friendly lead-free CsBi3I10-based perovskite solar cell has been numerically analyzed.•Enhancement of open circuit voltage (VOC) up to 360 mV has been observed after introduction of NiOx HTL.•The influence of key defect parameters of the CsBi3I10 absorber and CeOx/CsBi3I10 interface layer have been extensively studied.•Exploration of energy band alignment impact on the device performance. Bismuth-based halide perovskite (CsBi3I10) is a promising absorber material for the fabrication of eco-friendly perovskite solar cells (PSCs). In this research, the performance of the CsBi3I10-based PSCs with different hole transport layers (HTLs) has been numerically analyzed. The open circuit voltage (VOC) has enhanced up to 360 mV after the addition of NiOx HTL in the heterostructure of the CsBi3I10-based PSC. A comprehensive numerical study of the role of band alignment, key defect parameters of the CsBi3I10 absorber layer, and CeOx/CsBi3I10 interface on the newly designed heterostructure (ITO/CeOx/CsBi3I10/NiOx/Au) performance of the CsBi3I10-based PSC has been conducted. A massive deterioration of the VOC has been initiated when defect concentration (Nt) of CsBi3I10 crosses above 1014 cm−3. Apart from the Nt, defect energy level within the bandgap (Et), and holes capture cross-section (σp) of the CsBi3I10 layer have also significantly affected the VOC loss. Besides, the investigation indicates that the device performance is almost independent of Et of the CeOx/CsBi3I10 interface and slightly decreases with the increase of Nt and σp. Finally, the photovoltaic performance of the PSC has been explored for various thickness and carrier concentration of the CsBi3I10, cerium oxide (CeOx), and nickel oxide (NiOx). Therefore, this research provides efficient guidelines for the fabrication of eco-friendly high-performance CsBi3I10-based PSCs.